Strengthening Educational Quality through Participatory Quality Management Assistance at MTs Al-Islam Poncol, Magetan - Iman, Nurul; Kurnianto, Rido; Ariyanto, Ayok (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
MTs Al-Islam Muhammadiyah Poncol, located in Magetan, faces several institutional challenges, including low student enrollment, poor public perception, limited infrastructure, and suboptimal service quality from its staff. These issues have resulted in diminished community trust and reduced interest from prospective students. This community service program aimed to enhance institutional capacity and improve the quality of educational services through the implementation of participatory and sustainable quality management practices. The program was carried out in several stages: initial coordination and socialization, a comprehensive SWOT analysis, in-depth discussions to identify priority issues, and training on Service Excellence and the 5R work culture (Ringkas, Rapi, Resik, Rawat, Rajin - sort, set in order, shine, maintain, and discipline). The program yielded tangible results, including increased awareness and commitment among school staff, improved collaboration with stakeholders, and better service behavior within the school. Notably, teachers and administrators demonstrated a readiness to adopt quality management principles into daily operations. The physical and behavioral changes observed indicate early signs of institutional transformation. The program also fostered a culture of continuous improvement and built a foundation for long-term development. As a result, this initiative has contributed to rebuilding the madrasah’s reputation, strengthening stakeholder satisfaction, and enhancing its potential to become a competitive Islamic educational institution. The participatory approach and collaboration with academic experts ensured that the program was well-targeted, contextually relevant, and has the potential to be sustained and replicated in similar educational settings